Alteration of gentamicin and cefazolin kinetics with control of the hypothyroid state in humans. - Chanson, P (1987)
We studied the effect of the control of the hypothyroid state in humans on the pharmacokinetic parameters of cefazolin and gentamicin after a single intravenous injection. These two antibiotics were chosen because of their different patterns of binding to serum albumin (0% for gentamicin and 82% for cefazolin). In hypothyroidism, the behavior of cefazolin only was altered, with a decrease in the total body clearance, possibly due to reduced urinary excretion, and a decrease in the volume of distribution without a significant alteration of cefazolin binding to serum protein.